Matching Degree Between University Students’ Digital Literacy and the Current Situation of Mobile Language Learning - Zhang, Kai; Pochuieva, Olha (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Based on the current situation of university students’ mobile phone language learning, this paper investigates whether university students’ digital literacy can effectively support their mobile phone language learning, aiming at clarifying the matching between university students’ digital literacy and the current situation of mobile phone language learning, and constructing corresponding application mechanisms. It is found that university students’ existing digital literacy can not effectively support their mobile language learning practices, which shows that the former has a significant impact on the application level of the latter. The two are significantly related in many elements, but the matching degree between many pairs of related elements is low and the deviation is large: the existing acquisition skill of digital literacy have a negative impact on the satisfaction and usefulness of mobile language learning; Low-level creative skill have a negative impact on the usefulness, convenience and satisfaction of mobile phone language learning. Therefore, measures such as promoting the development of general digital literacy to specialized digital literacy, adopting digital literacy promotion plan that integrate daily contact and training interventions, carrying out teaching activities based on low deviation matching, and using demographic characteristics to adjust digital literacy can improve the level of mobile language learning adoption.